Physicochemical and tribological properties of gemini-type halogen-free dicationic ionic liquids - Qiangliang Yu; Chaoyang Zhang; Rui Dong; Yijun Shi; Yurong Wang; Yanyan Bai; Jiaying Zhang; Meirong Cai; Feng Zhou; Weimin Liu (Friction)
Abstract A series of new halogen-free dicationic ionic liquids (ILs) with different alkyl chain lengths were prepared, and the relationship between the alkyl chain length, physicochemical and tribological properties of ILs, and their role as neat lubricant for steel-steel friction pairs, was investigated. Evaluation of stability during hydrolysis and copper strip corrosion test results show that synthetic ILs are stable and not corrosive to metal contacts, due to the halogen-free anions. The friction and wear test results indicate that ILs with long alkyl chains have excellent friction-reducing and anti-wear properties, especially at high temperatures. Based on the surface three-dimensional (3D) profiles, electrical contact resistance, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and the X-ray photoelectron spectrometry (XPS) analysis of the worn surfaces of steel discs, we can conclude that the efficiency of ILs is due to the formation of high quality tribofilms that consist of both tribochemical reaction and ordered absorption films.